UNDERSTANDING THE INTERPLAY OF FIRM SIZE, AUDIT FEES, AND AUDIT FIRM SIZE IN SHAPING FINANCIAL REPORT QUALITY: EMPIRICAL EVIDENCE FROM ASEAN COUNTRIES - Witjaksono, Armanto; Leidessya, Andrea (Journal of Applied Finance and Accounting, 2024)
This study investigates the impact of firm size, audit fees, and audit firm size on financial report quality, along with examining variations in financial report quality across ASEAN countries. A sample of 164 manufacturing companies listed in ASEAN countries during the 2018-2021 period was selected using a purposive sampling method. Pooled data regression and Kruskal-Wallis nonparametric analysis were employed for data analysis. The findings reveal that firm size and audit fees have a significant negative influence on financial report quality, while audit firm size does not exhibit a significant effect. Furthermore, notable variations exist in the quality of financial reports among ASEAN countries. These results provide empirical evidence that auditing services alone do not enhance financial report quality, underscoring the need for practitioners, academics, and regulators to undertake necessary measures for improving the quality of companies' financial reports.